Antibiotic consumption trends in Ghana: analysis of six-years pharmacy issue data from a secondary healthcare facility - Obeng-Nkrumah, N.; Labi, A.K. (JAC Antimicrobial Resistance, 2023)
Background: Surveillance of hospital antibiotic consumption provides data to inform corrective action and for monitoring antimicrobial stewardship activities. This study described antibiotic consumption patterns from 2016 through 2021 at a secondary healthcare facility in Ghana. Methods: Using the WHO methodology for surveillance of antimicrobial consumption in hospitals, we analysed a 6-year pharmacy issue data at the Eastern Regional Hospital. We report on the defined daily dose (DDD) per 100 patients, types of antibiotics consumed according to Anatomic Therapeutic Classification (ATC), WHO AWaRe classification; trends in antibiotic consumption and expenditure per DDD of antibiotics consumed. Results: Over the period, the mean (±standard deviation) antibiotic consumption rate was 256.7 ± 33 DDD/100 patients per year. A linear regression model showed an insignificant decreasing trend in antibiotic consumption (coefficient for time –0.561; P = 0.247). The top three consumed antibiotics in DDD/100 patients at ATC level 5 were amoxicillin-clavulanate (n = 372.6), cefuroxime (n = 287.4) and sulfamethoxazole-trimethoprim (n = 145.8). The yearly Access-to-Watch ratio decreased from 2.4 in 2016 to 1.2 in 2021. The mean yearly cost of antibiotics was $394 206 ± 57 618 US dollars. The top three antibiotics consumed in terms of cost were clindamycin $718 366.3, amoxicillin-clavulanate $650 928.3 and ceftriaxone $283 648.5. Conclusion: This study showed a sturdy rate of antibiotic consumption over the 6-year period with a year-on year decrease in the Access-to-Watch antibiotic ratio. Data from pharmacy drug issues offer an opportunity to conduct antibiotic consumption surveillance at the hospital and national level in Ghana.
Research Article
Keywords: antibiotic consumption; antimicrobial; Ghana